Diverse modes of binding in structures of Leishmania major N-myristoyltransferase with selective inhibitors. (2014) - Brannigan, J. A.; Roberts, S. M.; Bell, A. S.; Hutton, J. A.; Hodgkinson, M. R.; Tate, E. W.; Leatherbarrow, R. J.; Smith, D. F.; Wilkinson, A. J.
No abstract available